A new species of salamander (Caudata: Plethodontidae, Bolitoglossa) from Sierra Nevada de Mérida, Venezuela - García-Gutiérrez, Javier; Escalona, Moisés; Mora, Andrés; de Pascual, Amelia Díaz; Fermin, Gustavo (Zootaxa, 2013)
In this article, a new species of salamander of the genus Bolitoglossa (Eladinea) from the cloud forest near La Mucuy in Sierra Nevada de Mérida, Venezuelan Andes, is described. Bolitoglossa mucuyensis sp. nov. differs from all Venezuelan salamanders, except B. orestes, by a larger SVL/TL ratio, and from La Culata salamander B. orestes by a reduced webbing extension of the front and hind limbs. Additionally, B. mucuyensis sp. nov. and B. orestes diverge 3.12% in terms of the nucleotide sequence of the 16S rRNA gene, as previously reported, and in 8.1% for the cytb gene as shown in this study.